Ethical and lingua-ecological characteristics of paremiological units of the Kazakh and Russian languages (Eurasian Journal of Philology Science and Education, 2023)
The article is devoted to the study of paremiological units of the Kazakh and Russian languages in the aspect of ethical lingua-ecology. The study is due to the growing interest of scientists in the ethical potential of proverbs, as well as insufficient consideration of proverbs in the speech-pragmatic aspect. Since these short words reflect people's conclusions and judgments, they make it possible to determine the nature of the ethical assessment (positive or negative) inherent in the speech. This article examines the proverbs of the Kazakh and Russian languages from the perspective of their ecological friendliness and non-ecological friendliness. It studies value models of behavior and stereotypical ideas that can harm the emotional balance of the listener. The article identifies the meanings of Kazakh and Russian paremias through various tasks and determines their ecological friendliness or non-ecological friendliness by analyzing the nature of their impact, whether positive or negative. This aspect of the study of proverbs is innovative, as previous works on linguistics only considered ethical concepts. To determine the nature of the impact of proverbs on the consciousness of communicants, the study used one hundred and five proverbs of the Kazakh and Russian languages, and the communicants had to determine the meaning of the proverbs and the nature of their impact. To clarify the hidden meaning of the paremiological unit through lingua-pragmatic analysis, the types of people's intentions manifested in the value system were determined. The study concludes that the development of ethical lingua-ecology should be aimed at studying ethical factors (proverbs) expressing ethical norms, as well as phenomena that harm human safety in the textual information environment.Keywords: ethical lingua-ecology, norms, proverbs, speech act, modeling experiment, threat, manipulation.